Estimasi Ketinggian Planetary Boundary Layer Berdasarkan Data Radiosonde Menggunakan Metode Gradien Vertikal Suhu Udara - Mantara; Jemakmun; Firamon Syakti; Merry Agustina (STMIK Budi Darma, 2023)
The part of the troposphere known as the Planetary Boundary Layer (PBL), which is directly influenced by the Earth's surface, has an important role in climate, weather and air quality. Many studies have succeeded in identifying the height of PBL using observational data such as radiosonde data. Based on existing data, in South Sumatra an area of ??736,587 hectares burned in 2015. When compared to other districts, OKI is one of the areas that experienced the most fires, namely 377,365 hectares of land in OKI were burned. A total of 361,857 Ha of land burned in 2019. The area with the most fires with an area of ??204,974 Ha is still OKI Regency. In this study using a descriptive method with a quantitative approach. To determine the height of the PBL in this study using the air temperature vertical gradient method. From the results of radiosonde data the maximum height of the radiosonde balloon on September 13, 2022 (00:12 UTC) is 26,257 masl and (12:00 UTC) is 26,151 masl, on September 14, 2022 (00:01 UTC) is 25,355 masl and (12 :00 UTC) is 26,182 masl, on September 15 2022 (00:00 UTC) is 27,723 masl and (06:00 UTC) is 27,250 masl. Based on the temperature gradient graph, it can be seen that the lowest PBL height is at 1,807 masl and The highest PBL is at an altitude of 2,884 masl